Does increasing the minimum wage reduce poverty in developing countries? - T. H. Gindling (IZA World of Labor, 2014)
Do minimum wage policies reduce poverty in developing countries? It depends. Raising the minimum wage could increase or decrease poverty, depending on labor market characteristics. Minimum wages target formal sector workers—a minority of workers in most developing countries—many of whom do not live in poor households. Whether raising minimum wages reduces poverty depends not only on whether formal sector workers lose jobs as a result, but also on whether low-wage workers live in poor households, how widely minimum wages are enforced, how minimum wages affect informal workers, and whether social safety nets are in place.
Keywords: O17; J31; I32; 330; minimum wages; developing countries; poverty